Development of buffer layer structure for epitaxial growth of (100)/(001)Pb(Zr, Ti)O3-based thin film on (111)Si wafer. (26th June 2017) - Hayasaka, Takeshi; Yoshida, Shinya; Tanaka, Shuji
Abstract: This paper reports on the development of a novel buffer layer structure, (100)SrRuO3 /(100)LaNiO3 /(111)Pt/(111)CeO2, for the epitaxial growth of a (100)/(001)-oriented Pb(Zr, Ti)O3 (PZT)-based thin film on a (111)Si wafer. (111)Pt and (111)CeO2 were epitaxially grown on (111)Si straightforwardly. Then, the crystal orientation was forcibly changed from (111) to (100) at the LaNiO3 layer owing to its strong (100)-self-orientation property, which enabled the cube-on-cube epitaxial growth of the subsequent (100)SrRuO3 layer and preferentially (100)/(001)-oriented PZT-based thin film. The PZT-based epitaxial thin films were comprehensively characterized in terms of the crystallinity, in-plane epitaxial relationships, piezoelectricity, and so forth. This buffer layer structure for the epitaxial growth of PZT can be applied to piezoelectric micro-electro-mechanical systems (MEMS) vibrating ring gyroscopes.